دراﺳﺔ ﻣﻘوﻣﺎت اﻟﺗﻐذﯾﺔ اﻟﺻﺣﯾﺔ ﻟدى طﻠﺑﺔ ﺟﺎﻣﻌﺔ ﻛرﺑﻼء (Journal of the College of Education for Women, 2019)
The aim of this study was to assess the nutrition status for students samples at the age of 18- 35 years, these samples were taken from Karbala university, 142 of them were male and 318 were female. Date on weight, height and body mass index (BMI) were determined for each individual. This samples were taken in order to record their nutritional behavior and daily food intake during the 24 hours prior to the visit through personal meeting using special questionnaire. The results showed that the weight and the height were within the range of the people of neighboring Arab countries, who are in the same age. Beside 63.28% for female and 58.33% for male were within the normal weight using body mass index. Percentages of overweight were between 30.90%- 25% and 10.62%- 17.92, for male and female, respectively. There was an increase in daily food intake in general for macronutrients and energy indeed. As recorded in nutritional behavior. 51% of samples following on mass media. There were 18% of the samples practicing regimen system and 20% have taken dietary vitamin and mineral supplements 22% of samples have suffers from malnutrition diseases. Type of obesity and slimness, anemia and the allergy, also notes in this study to percent 57% of these samples was not consultations the doctors about eat dietary supplements. In general their daily food intake were above That showed by American recommended daily dietary, also fewness the case mal nutrition diseases. Still there was some incorrect nutritional behavior which need more program education and learning about nutrition.